Evidence-Based Educational Practices for Public Health: How We Teach Matters. (June 2021) - Godley, Sophie; Aumiller, Betsy; Horigian, Viviana; Khalil, Naila; Kruger, Jessica; Pennel, Cara; Youatt, Emily; Kiviniemi, Marc T.
An eight-member team of the Teaching Working Group of the Association of Schools and Programs of Public Health Scholarship of Teaching and Learning Task Force created a call to action advancing the use of evidence-based strategies for public health education. The goal of this article is threefold, to assess briefly the current status of evidence-based teaching in public health, strengthen the case for using evidence-based teaching practices in public health courses, and propose strategies for educators in public health to engage along a continuum of evidence-based teaching. In this article, we define evidence-based teaching (EBT) proposes that EBT is demonstrated by: student mastery of specific short-term learner outcomes (e.g., enhanced effectiveness such as represented by improved knowledge, skills, and/or attitudes); increases the likelihood of successfully completion of a particular public health degree or program, which represents an intermediate- or long-term outcome; and ultimately posits that effective teaching in public health aims to produce well-prepared graduates who contribute to a ready workforce (Impact 1) who are able to improve the health of the public (Impact 2), highlights effective evidence-based teaching practices that improve student learning outcomes, encourages both seasoned faculty and newcomers to the field to incorporate EBT into existing public health curricula and to begin by making small changes, and concludes with a call to action for EBT that improves student learning.